Mine, Theirs or Ours? A Multi-Country Experiment on Citizens' Motivations to Invest in Mental Health - Pierluigi Conzo; Marina Della Giusta; Florent Dubois; Giovanni Razzu; Giacomo Rosso (Institute of Labor Economics (IZA), 2025)
Mental health is vital for well-being and productivity, yet investment remains chronically low. We study how different framings of mental health investment affect cooperation and donations using a pre-registered online experiment across five European countries (N = 8,312). Participants were randomly assigned to receive information emphasizing either individual benefits (Private Perspective), collective benefits (Public Perspective), or prevalence data (Neutral Perspective). All treatments significantly increase cooperation in a Public Goods Game and donations in a Charity Dictator Game, suggesting intrinsic motivation drives behavior. Only the Private Perspective increases personal normative expectations, while empirical expectations remain unaffected–suggesting that interventions influence moral beliefs more than beliefs about others' actions. All treatments reduce self-reported mental health stigma, consistent with evidence from a list experiment, suggesting stigma reduction as a key mechanism. Heterogeneity analyses show stronger treatment effects among individuals with lived experience or prior concern, and reduced contributions under collective framings when public provision is perceived as adequate–consistent with a substitution effect between public and private action. Donations also decline in post- communist countries, aligning with historically lower institutional trust and weaker norms of private giving. These findings highlight how individual perceptions and institutional legacies shape behavioural responses, and suggest that perceived adequacy of public provision can backfire by discouraging private engagement–potentially trapping societies in a bad equilibrium of persistent underinvestment in mental health.
Keywords: C90; I12; I18; I31; 330; mental health; cooperation; donations; stigma; online survey experiment; information treatment